El masaje infantil: conocimientos, experiencias y opiniones de profesionales de Enfermería Ginecobstétrica y Perinatal. - López Quirós, Laura Patricia (2009)
The article presents the results of an investigation that had as main objective to analyze the knowledge, experience and views of professionals and nursing Gynecobstetric and perinatal about the infant massage, those specialists work in hospitals and private clinics in San Jose. The study was conducted in the period December 2007 to June 2008, and developed a quantitative approach and transactional as methodologically exploratory. It should be stressed that after of the investigation and review of the respective literature, there were no studies directly linking the practice of infant massage with Gynecobstetric and perinatal nursing. The population consisted of Gynecobstetric and perinatal nurses who worked in the areas of maternal and neonatal care in hospitals and private clinics in San Jose. The data collection was carried out by applying a questionnaire. The analysis results are presented through descriptive statistics. The research showed that nurses and nurse midwives have a general knowledge of the importance of infant massage but do not know the techniques to do or to teach it. It also stressed that nurses and midwives of the study participants were considered the apt person to teach infant massage, because of their direct care interventions with parents and their babies and cause they`re willing to do it.